Beyond piety and politics: religion, social relations, and public preferences in the Middle East and North Africa - Ciftci, Sabri (Middle East studies, 2022)
Introduction -- 1. Religious Communities, the State, and Religious Outlooks -- 2. Attitudes of the Devout: The Nature of the Substance or the Nurture of Relationship? -- 3. Empirical Foundations of Religious Outlooks -- 4. The Individual and Contextual Determinants of Muslim Religious Outlooks in MENA -- 5. Islam and Support for Democracy -- 6. Temporal Change in Religious Outlooks and Political Preferences -- 7. Islam and Distributive Preferences -- Conclusion -- Appendix A -- Appendix B -- Bibliography -- Index.